Decimeter‐scale in situ mapping of modern cross‐bedded dune deposits using parametric echo sounding: A new method for linking river processes and their deposits. Issue 15 (1st August 2013) - Sambrook Smith, Gregory H.; Best, James L.; Orfeo, Oscar; Vardy, Mark E.; Zinger, Jessica A.
Abstract : [1] Collecting high‐resolution data to quantify the sedimentary architecture within contemporary alluvial channels remains one of the outstanding challenges in fluvial sedimentology. Here, we present data collected using a new geophysical method, the parametric echo sounder (PES), which can meet this challenge. From surveys over a field of sand dunes in the Río Paraná, Argentina, we demonstrate the unique ability of PES to image the subsurface structure within active channels at a decimetric resolution. These data reveal the bounding surfaces between bars and dunes, as well as the foresets and reactivation surfaces within them. This provides quantitative in situ data for recent work that suggests cross‐strata preserved by dunes may be more related to flow depths less than the commonly assumed bankfull level. These surveys demonstrate that PES can provide hitherto unobtainable data from alluvial channels and presents significant opportunities for more detailed coupled studies of fluvial processes and their deposits. Key Points: A parametric echo sounder images fluvial dune deposits for the first time Parametric echo sounding images channel deposits at a decimetric resolution Dune cross‐sets may not relate to the commonly assumed bankfull level